Overview of Crown Gear Coupling Contact Theory - Guan Yongqiang; Wang Jianmei; Ning Ke; Wang Bo (Jixie chuandong)
Due to special tooth surface morphology, the crown gear coupling achieves misalignment compensation while causing the non-uniform carrying of tooth pairs, which destroys the stability of the tooth surface contact. Scholars at home and abroad have carried out extensive research on the contact theory of tooth pairs, reviewed the contact characteristics and the theoretical research of crown gear couplings, and pointed out the contact theory model of clearance of tooth pairs, contact stress of tooth surface, and load distribution of tooth pairs, which is the key technology to achieve the optimal design of high-performance crown gear couplings.